Dosing frequency and adherence in chronic psychiatric disease: systematic review and meta-analysis - Medic G (Dove Medical Press, 2013)
Goran Medic,1 Kyoko Higashi,1 Kavi J Littlewood,1 Teresa Diez,2 Ola Granström,3 René S Kahn41MAPI Consultancy, Houten, The Netherlands; 2AstraZeneca, Zaventem, Belgium; 3AstraZeneca, Södertälje, Sweden; 4Division of Neuroscience at the Utrecht University Medical Center, Utrecht, The NetherlandsBackground: The purpose of this study was to investigate the impact of dosing frequency on adherence in severe chronic psychiatric and neurological diseases.Methods: A systematic literature review was conducted for articles in English from medical databases. Diseases were schizophrenia, psychosis, epilepsy, bipolar disorder, and major depressive disorder.Results: Of 1420 abstracts screened, 12 studies were included. Adherence measures included Medication Event Monitoring System (MEMS®), medication possession ratio, medication persistence, and refill adherence. Three schizophrenia and one epilepsy study used MEMS, and all showed a trend towards higher adherence rates with less frequent dosing regimens. Three depression and one schizophrenia study used the medication possession ratio; the pooled odds ratio of being adherent was 89% higher (ie, 1.89, 95% credibility limits 1.71–2.09) on once-daily versus twice-daily dosing. Two studies in depression and one in all bupropion patients assessed medication persistence and refill adherence. The pooled odds ratio for the two depression studies using medication persistence was 2.10 (95% credibility limits 1.86–2.37) for once-daily versus twice-daily dosing. For refill adherence after 9 months, 65%–75% of patients on once-daily versus 56% on twice-daily dosing had at least one refill. In all but one of the studies using other measures of adherence, adherence rates were higher with once-daily dosing compared with more frequent dosing regimens. No relevant studies were identified for bipolar disorder or psychosis.Conclusion: Differences in study design and adherence measures used across the studies were too large to allow pooling of all results. Despite these differences, there was a consistent trend of better adherence with less frequent dosing.Keywords: adherence, dosing frequency, schizophrenia, epilepsy, depression